THEORETIC OBSERVATION OF THE COTTON MOVEMENT IN THE OPERATING CAMERA OF THE NEW SEPARATOR - Pirnazarov, Ulugbek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The Studies moving the pat product in its raw state in worker to camera of the separator to new design. In given article explored moving the pat-product in its raw state in worker to camera of the separator in new designs. Will Formed differential equation moving the pat and are received analytical decision, characterizing laws motion from time.